El juego constructivo en el desarrollo de la creatividad en niños y niñas de la institución educativa inicial N°344 Mi primer aprendizaje, distrito de Punchana 2022 - Marreros Huaymacari, Perla Margarita (2024)
The general objective of the study is to determine the relationship between constructive play and the development of creativity in boys and girls of the initial educational institution No. 344 My First Learning, Punchana district, 2022. The type of research is descriptive - quantitative, the cross-sectional correlational design, to collect the information, an observation guide was used for the constructive game and for the development of creativity variable, also an observation guide. The sample for the present study was 252 children from the initial level. The study concludes, through the Pearson correlation coefficient of 0.567, this indicates a moderate direct and positive relationship between both variables, this means that by using constructive play, children can enhance their creative development.